Tito Puente, Mambo King = Tito Puente, Rey del Mambo - Brown, Monica, 1969- (HarperCollins Publishers, 2013)
A vibrant bilingual picture-book biography that portrays the musical and cultural phenomenon of Tito Puente, Mambo King.